KONSEP SMART ENVIRONMENT TERHADAP PENYEDIAAN RUANG TERBUKA HIJAU (STUDI KASUS: KOTA BANDAR LAMPUNG) - Rilansari, Valendya (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) ITERA, 2024)
The concept of smart environment has an embodiment to protect, restore and manage the utilization of terrestrial ecosystems in the form of green open spaces to avoid a decrease in their area in line with the concept of sustainability. The concept of smart environment is supported by the achievement of the 11th sustainable development goal, namely in the pillar of natural resource management including green areas. With the concept of smart environment, green open spaces (GOS) can be fulfilled, especially in Bandar Lampung City by examining important aspects that need to be considered. This study uses qualitative descriptive analysis based on literature studies related to the concept of smart environment in big cities around the world and Indonesia. Then, a comparison is described regarding policies, implementation, and recommendations, especially the provision of GOS. In the end, the findings of the study describe the concept of smart environment as an effort to provide GOS in Bandar Lampung City based on policies that pay attention to economic, social and environmental aspects which produce recommendations in the form of Tree Planting, Socialization and Education from an early age, Cross-Sector Cooperation, Promotion of Biodiversity, Food Security, Development of Blue-Green Infrastructure, and Expansion of the Provision of City Parks.